The archaeology of North American farmsteads - Groover, Mark D. (American experience in archaeological perspective., 2008)
From the early colonial period to the close of World War II, life in North America was predominantly agrarian and rural. Archaeological exploration of farmsteads unveils a surprising quantity of data about rural life, consumption patterns, and migrations across the continent. Mark Groover offers both case studies and an overview of current trends in farmstead archaeology in this exciting new work. He also proposes a research design and makes numerous suggestions for evaluating (and re-evaluating) the significance of farmsteads as an archaeological resource. His chronological survey of farmstead sites throughout numerous regions of North America provides fascinating insights to students, cultural resource management professionals, or general readers interested in learning more about what material culture remains can teach us about the American past. - Publisher.